Evaluasi Perataan Laba pada Kinerja Badan Usaha Milik Negara Sebelum dan Setelah Menjadi Perusahaan Terbuka di Indonesia - Bambang Prayogo; Itjang D.Gunawan (INDONESIAN JOURNAL OF ACCOUNTING AND GOVERNANCE, 2018)
This study was investigated by using multiple regression analysis method. The sample of this research is purposive sampling with total 6 years observation. The result of the research shows that SOEs conduct earnings management policy in two years before IPO and two years after IPO by income increasing. In order to get generalized results future research can use all listed state-owned enterprises until 2016, which is 20 companies with five years-period before and after going public.